Teaching English to Young Learners: Evidence from Kampus Mengajar Practice - Malkhah Tyas Labaika; Sugeng Purwanto (research, training and philanthropy institution Natural Aceh, 2023)
In 2020, Nadiem Makarim (Minister of Education, Culture, Research, and Technology of Indonesia) launched the Merdeka Belajar-Kampus Merdeka (MBKM) program for the scope of higher education by giving students the right to take courses outside the study program for one (1) semester and do activities outside the university for two (2) semesters This study is significant can provide insight into learning strategies that can be used to teach early childhood and provide views on information and references in the field of basic education regarding materials suitable for use in learning elementary school children. This research used a qualitative descriptive, moving on a simple qualitative approach to get a result. The research objective is descriptive of the topic posed and studied. The research results obtained are later translated and described in clear explanations so that the results obtained can be clearly explained. The data collection was conducted by observation, data checklist, and interview. The result of this study is improved students' grades and understanding of English after using the new learning method, singing, flashcard, Questions and Answer, and Quizzes.